151k views
2 votes
Changing the subject of a formula making x the subject of each formula

Changing the subject of a formula making x the subject of each formula-example-1
User Edi Wang
by
4.8k points

1 Answer

2 votes

As per given by the question,

there are given that the equation,


(1)/(2)x=u+6

Now,

From the given equation,


(1)/(2)x=u+6

Then,


\begin{gathered} (1)/(2)x=u+6 \\ (1)/(2)x-u-6=0 \end{gathered}

Then,


\begin{gathered} (1)/(2)x-u-6=0 \\ (1)/(2)x=u+6 \\ x=(u+6)/((1)/(2)) \\ x=2(u+6) \end{gathered}

Hence, the value of the x is,


\begin{gathered} x=2(u+6) \\ x=2u+12 \end{gathered}

For Part 7:

The given equation is,


1-13w=2h+x

Then,


\begin{gathered} 1-13w=2h+x \\ 1-13w-2h-x=0 \\ 1-13w-2h=x \end{gathered}

Hence, the value of x is,


x=1-13w-2h

Now,

For part 10:

The given equation is,


5=x-21+q

Then,


\begin{gathered} 5=x-21+q \\ 5-x+21-q=0 \\ 26-x-q=0 \\ x=-q+26 \end{gathered}

Hence, the value of x is,


x=-q+26

User Amy Obrian
by
4.9k points